2018
DOI: 10.1515/jpem-2018-0140
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic risk factors in preschool children with abdominal obesity from Medellín, Colombia

Abstract: Background Abdominal obesity (AO) is linked to inflammation and insulin resistance (IR). However, there is limited information on whether preschoolers with AO present these risk factors. We evaluated the association between AO and cardiovascular risk factors in preschoolers. Methods We enrolled 232 children (2–5 years), of whom 50% had AO. Serum total cholesterol (TC), low-density lipoprotein-cholesterol (LDL-c), high-density lipoprotein-cholesterol (HDL-c), triglycerides (TG), apolipoprotein B (Apo-B) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 35 publications
3
9
0
1
Order By: Relevance
“…The analysis of anthropometric variables according to weight status has confirmed that each component of the MetS worsens with increasing weight, independent of sex (27). As has been reported previously (26,28,29) and was found in our study, several parameters did not show significant differences between overweight and obese children, except for a significantly higher WC in the obese group, which reinforces its importance as a risk indicator. The impaired levels of insulin, HOMA-IR, TG, HDL-C, and total-and HMW-adiponectin in the obese group compared to the normal group confirm the remarkable impact of obesity on metabolic disorders.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The analysis of anthropometric variables according to weight status has confirmed that each component of the MetS worsens with increasing weight, independent of sex (27). As has been reported previously (26,28,29) and was found in our study, several parameters did not show significant differences between overweight and obese children, except for a significantly higher WC in the obese group, which reinforces its importance as a risk indicator. The impaired levels of insulin, HOMA-IR, TG, HDL-C, and total-and HMW-adiponectin in the obese group compared to the normal group confirm the remarkable impact of obesity on metabolic disorders.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding biochemical parameters, total-adiponectin had the strongest inverse correlation respect to HMW adiponectin, with glycaemia, followed by number of MetS components, HOMA-IR and insulin concentration. Similar findings have been described, where total adiponectin had a significant inverse relation with HOMA-IR and obesity, and its low concentration was an essential determinant of insulin sensitivity and HDL in children and may predict type 2 diabetes (7,29,32,34,35). No significant correlation was found for biochemical parameters related to fat metabolism (e.g., TG, HDL-C, LDL-C and TChol), probably due to the young age of the population and the pathophysiology of MetS (24,36).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Considering that fatty acid consumption is a strong AHEI component and is assessed based on three criteria, this index might be associated with abdominal obesity. Such an approach could provide useful insights to determine whether further health interventions should be employed in Colombia, where waist circumference and other measures of obesity have been associated with cardio-metabolic markers in young children (28) .…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Other local studies showed a prevalence of 50.4% and 50% of AO in Spanish and Colombian preschoolers, respectively, but up-to-date information is not available for the entire country. 34,35 Therefore, the purpose of this study was to determine the association between the lifestyles of children (i.e., MD, PA, and ST) with AO of preschoolers from three Spanish-speaking countries (Chile, Colombia, and Spain) with different socioeconomic levels and HDI indicators.…”
mentioning
confidence: 99%